A journey through the last dance : - DeSpelder, Lynne Ann (McGraw-Hill, 2005)
This is a wise and well written book, attested by the many editions it has run. Yet it has as a its basic assumption the startling discovery that Americans begin this last dance, death, with not much preparation and usually with the sudden announcement of some life threatening illness of one sort or another. So, it seems, all those involved in the so-called death system of America are not prepared to deal with death on a moments notice, much like a crash course. This was not the case, as the authors demonstrate, with either Native Americans or Americans in the, say, 1900's. The contrast is no accident.